2023
DOI: 10.1507/endocrj.ej22-0457
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular complications in insulin resistance and endocrine diseases

Abstract: Cerebrovascular diseases, such as stroke and cardiovascular disease, are one of the leading causes of death in Japan. Type 2 diabetes is the most common form of diabetes and an important risk factor for these diseases. Among various pathological conditions associated with type 2 diabetes, insulin resistance has already been reported to be an important risk factor for diabetic complications. The major sites of insulin action in glucose metabolism in the body include the liver, skeletal muscle, and adipose tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…It was shown that gluconeogenesis is suppressed by insulin signaling mediated by IRS-1/2 in the proximal tubules, and impaired insulin signaling in the tissue leads to systemic insulin resistance [31]. We also showed that inactivation of the forkhead box O 1 (FoxO1), one of the key downstream molecules of insulin signaling [3,33], via interaction with peroxisome proliferator-activated receptor gamma coactivator (PGC) 1α, is important in this context [31], although the contribution of the mammalian target of rapamycin (mTOR) pathway was also proposed recently [28]. Insulin receptor is considered to be expressed in the basolateral side of the proximal tubules [34], but glucose reabsorbed by SGLT1/2 expressed on the luminal side of the proximal tubules was also shown to suppress gluconeogenesis via suppression of Sirtuin 1 activity (Fig.…”
Section: Insulin Regulates Gluconeogenesis In the Proximal Tubules Of...mentioning
confidence: 89%
“…It was shown that gluconeogenesis is suppressed by insulin signaling mediated by IRS-1/2 in the proximal tubules, and impaired insulin signaling in the tissue leads to systemic insulin resistance [31]. We also showed that inactivation of the forkhead box O 1 (FoxO1), one of the key downstream molecules of insulin signaling [3,33], via interaction with peroxisome proliferator-activated receptor gamma coactivator (PGC) 1α, is important in this context [31], although the contribution of the mammalian target of rapamycin (mTOR) pathway was also proposed recently [28]. Insulin receptor is considered to be expressed in the basolateral side of the proximal tubules [34], but glucose reabsorbed by SGLT1/2 expressed on the luminal side of the proximal tubules was also shown to suppress gluconeogenesis via suppression of Sirtuin 1 activity (Fig.…”
Section: Insulin Regulates Gluconeogenesis In the Proximal Tubules Of...mentioning
confidence: 89%